Fatal laryngeal obstruction in a child by a balloon: A case report - Kumar, Narendra B; Bale, Priyanka G; Kukde, Hemant G; Dere , Rajesh C (Journal of Indian Academy of Forensic Medicine, 2019)
Choking is a condition caused by inhalation of a foreign. Balloon aspirations are highly fatal and are the number one cause of non-food related choking deaths in children. We present a case of an 18 months old male child brought to the Department of Forensic Medicine for postmortem examination with an alleged history of death due to aspiration of the balloon. The deceased was playing with a balloon and then suddenly started having difficulty in breathing and bluish discoloration of the face. He was immediately rushed to a hospital where he was declared brought dead. At autopsy, a yellow colored balloon was found completely obstructing the airway. The application of continuous suction forces to the un-inflated or partially air-filled balloon is considered the most crucial factor in causing asphyxiation by a rubber balloon. Education of parents, child care providers and preschool teachers along with product labeling describing hazards must be made a routine to avoid such fatalities.